Mycosis fungoides unveiled following dupilumab treatment in a patient with a history of atopic dermatitis. Usefulness of HFUS in monitoring skin features. A review with a case report - Cisoń, Hanna; Cisoń, Wiktor; Białynicka-Birula, Barbara; Suseł, Marianna; Białynicki-Birula, Rafał; Szepietowski, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Dupilumab has revolutionized atopic dermatitis (AD) treatment, but concerns arise about its potential link to cutaneous T-cell lymphomas (CTCL). This review explores CTCL occurrence post-dupilumab therapy in AD and its potential therapeutic effects. A case study of a 76-year-old patient with severe AD treated with dupilumab, developing erythroderma revealing mycosis fungoides (MF), underscores the need to understand associated mechanisms and risk factors for safe dupilumab use. This case also highlights the utility of the high-frequency ultrasound in monitoring cutaneous manifestations in patients with MF.